Financial Performance as a Mediator of Risk Management on Organizational Performance - Mardiana, Mardiana (MEC-J (Management and Economics Journal), 2021)
Sharia Bank is a bank that conducts business activities based on sharia principles, or Islamic legal principles stipulated in the fatwa of the MUI such as the principles of justice and balance, benefit, universalism. This study aims to examine the effect of risk management represented by Capital Adequacy Ratio (CAR), Operational Efficiency (BOPO), and Nonperforming Loans (NPL), on organizational performance by mediating financial performance that is represented by Return on Assets (ROA) on Sharia Banking Companies recorded in IDX from 2013 up to 2017. The data used in this study were obtained from their Financial Statements. After passing the purposive sample stage, six Islamic Banking companies recorded in IDX were eligible for use. The results of the study show that risk management influences organizational performance, while financial performance does not mediate the effect of risk management on organizational performance. Thus, Sharia banking operations must be adjusted to sharia principles and the bank is expected to pay more attention to the efficiency of the operations to improve risk management. Companies must think about the benefits and risks of lending funds to other parties so that the company value remains optimal.